Marriage in contemporary Japan - Tokuhiro, Yoko (Routledge contemporary Japan series, 2010)
This is the first book in recent years to explore the contemporary state of marriage in Japanese society. Setting out the different perceptions and expectations of marriage in today's Japan, the book discusses how economic issues and the family impact on marital behaviour.